2014
DOI: 10.1037/a0036640
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of misfortune: Deservingness, self-esteem, and patterns of self-defeat.

Abstract: Drawing on theorizing and research suggesting that people are motivated to view their world as an orderly and predictable place in which people get what they deserve, the authors proposed that (a) random and uncontrollable bad outcomes will lower self-esteem and (b) this, in turn, will lead to the adoption of self-defeating beliefs and behaviors. Four experiments demonstrated that participants who experienced or recalled bad (vs. good) breaks devalued their self-esteem (Studies 1a and 1b), and that decrements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 123 publications
(182 reference statements)
2
33
1
4
Order By: Relevance
“…[48]. In a similar vein, Callan and colleagues found that individuals who held stronger beliefs that they deserved bad outcomes engaged in more self-defeating behaviors, including self-handicapping, wanting close others to evaluate them negatively, and seeking negative feedback about their performance during an intelligence test [22]. On the other hand, adopting the belief that one deserves a fulfilling and meaningful life in the future may lead to greater general well-being in the face of illness cf.…”
Section: Discussionmentioning
confidence: 91%
“…[48]. In a similar vein, Callan and colleagues found that individuals who held stronger beliefs that they deserved bad outcomes engaged in more self-defeating behaviors, including self-handicapping, wanting close others to evaluate them negatively, and seeking negative feedback about their performance during an intelligence test [22]. On the other hand, adopting the belief that one deserves a fulfilling and meaningful life in the future may lead to greater general well-being in the face of illness cf.…”
Section: Discussionmentioning
confidence: 91%
“…Specifically, participants read several scenarios that described otherwise "neutral" people either being the beneficiaries of a fortuitous positive outcome (low justworld threat; cf. Callan, Kay, & Dawtry, 2014;Lerner, 1965), or the victims of a fortuitous negative outcome (high just-world threat), and rated the target persons in both relative and absolute terms. This design allowed us to examine whether the interactions observed in Studies 2a and 2b could be replicated in contexts where the person's conduct was not objectively tied to his or her outcome (unlike the "non-innocent" James, who brought about his own suffering by jaywalking).…”
Section: Studymentioning
confidence: 99%
“…Кроме того, метаиндивидуальная модель деструктивности обеспечивает концептуальные предпосылки (конструктную валидность) для создания нового (многофакторного) инструмента измерения деструкции. (Baumeister, Scher, 1988), негативное мнение о себе (Lundh et al, 2007;Renaud, McConnell, 2007), заслуженное самонаказание (Callan et al, 2014), ментальное поражение, утрата самоидентичности (Ehlers et al, 1998(Ehlers et al, , 2000, бессилие (Frederick, 1986;Herman, 1992), склонность личности испытывать неприязнь и быть придирчивой к себе, бояться успеха и счастья (Hyler, Rieder, 1987) Обладание Власть над людьми Стремление к превосходству, вмешательство, давление…”
Section: негативный деструктивный мирunclassified